Shirt Screen Printing Training as Creative Economic Empowerment for Village Youths - Nurhikmah, Nurhikmah; Al Ayyubi, Ibnu Imam; Prayetno, Eko; Martini, Sofia; Musaldin, La Ode (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Screen printing training as a form of creative economic empowerment for youth of Lempangang Village, especially Karang Taruna members, aims to improve technical and entrepreneurial skills. This research uses a qualitative approach with descriptive method, which involves observation, interview, and documentation during the training. The results showed that the training was successful in improving participants' shirt screen printing skills, providing new insights into entrepreneurship, and motivating them to start an independent business. The constraints faced included limited tools and materials, but the enthusiasm of the participants and the support of the Karang Taruna board gave hope for the development of creative businesses in the future. This training not only enriches skills, but also opens economic opportunities that can improve the welfare of rural communities through creative-based businesses.